IDENTIFIKASI TATA BUSANA SEBAGAI PENANDA STATUS SOSIAL FILM ORANG KAYA BARU (2019) - Yrviana, Dwi Ermy; Yeni Astuti, Soekma; Angelina, Dewi (ASKARA: Jurnal Seni dan Desain, 2025)
In films, clothing is the most important part of forming the character of the character being played. The clothing in the 2019 film Orang Kaya Baru can function as a marker of the character's change in social status from lower class to upper class. In society, social status cannot be seen from the dressing style of each individual because each person has a different dressing style. This is very different in films, in films clothing is very important to show social status. Based on the analysis carried out by researchers on the characters mother, Duta, Tika, and Dodi in the 2019 film Orang Kaya Baru, character changes can be seen from the clothes they wear. This research uses Ferdinand de Saussure's semiotic theory to identify changes in clothing worn by Ibu, Duta, Tika, and Dodi in the 2019 film Orang Kaya Baru. The type of research used is qualitative research with descriptive methods. The results of the research were four figures who were analyzed based on visual scenes with characteristic mise en scene aspects with a research focus on clothing that could indicate changes in social status. Changes in a character's clothing can be a sign and sign of a change in social status. Keywords: Semiotics, Clothing, Social Status